Cattle excreta on Lotus tenuis-promoted grasslands: Exploring soil microbiome and nitrous oxide emissions in the Salado River Basin, Argentina - Nieva, Amira Susana del Valle (2026)
Cattle production generates inputs such as urine and dung that increase soil microbial diversity by adding organic matter and nitrogen. Legume pastures, such as Lotus tenuis improve soil quality by incorporating nitrogen, influencing microbial communities, and contributing to nitrous oxide (N2O) emissions. This study aimed to investigate the impact of livestock and pasture systems on soil microbiomes and N2O emissions within grassland ecosystems. We analysed microbial communities in soils of natural and L. tenuis-promoted grasslands, using Next Generation Sequencing (NGS) and simulated urine and dung depositions in field mesocosms. The results revealed significant differences in microbial diversity between natural and L. tenuis-promoted grasslands across cattle input treatments. Biomarker analysis identified distinct phyla in each type of excreta and grassland system. In natural grasslands, Proteobacteria and Actinobacteriota were prevalent with urine, whereas Acidobacteriota and Verrucomicrobiota characterised the soils promoted by L. tenuis. The indicators of the dung-treated soils were Pseudonocardia, Flavobacterium, NP-4, Adhaeribacter, Pseudoxanthomonas, and Novosphingobium, while Brevundimonas, Defluviicoccus, Sphingomonas, Sphingomicrobium, REEP01, Chthoniobacter, Hyphomicrobium, and PSRF01 were microbial indicators of the urine-treated soils. The N2O emissions were significantly lower in fields with L. tenuis and urine addition compared to natural grasslands under similar conditions, with genera like Brevundimonas, Hyphomicrobium, and Nitrosocosmicus positively correlated with emissions. These findings underscore the role of pasture composition in shaping soil microbiomes and highlight the benefits of legumes, such as L. tenuis, in reducing N2O emissions, providing an alternative for more sustainable livestock management practices.